Hot-Fit Model pada Sistem Informasi Manajemen Rumah Sakit (SIMRS) di RSUD Pariaman - Rezi Kurnia Putri, Arifah Devi Fitriani, Asriwati (Journal of Health and Medical Science, 2024)
The application of the Hospital Management Information System (MISH) is very important to integrate all the information generated in the service process. At this time MISH in Pariaman Hospital continues to grow to improve service and hospital quality. However, there are still several factors that influence the implementation of MISH, namely the human component, the organizational component and the technology component. The purpose of this study was to evaluate the HOT-FIT model on the Hospital Management Information System (MISH) at Pariaman Hospital. The research design used was qualitative research. The key informants in this study were MISH users, totaling 6 people, while the triangulation informants were 1 person. Qualitative data collection techniques using the Triangulation method. Data analysis in this study used a qualitative descriptive. The results of the study indicate that the human factor must be supported by an adequate number of human resources and the placement of human resources in hospital departments must be appropriate. Organizational factors must provide a manual for the use of MISH, conduct MISH training once a year, evaluate MISH and use MISH every year. The technology factor used to support the implementation of MISH must be made faster. The conclusion of this study is that there is a match between human factors, organizational factors, and technology factors in generating net benefits at Pariaman Hospital. This is because human factors, organizational factors, and technology factors support each other. It is hoped that the management of Pariaman Hospital will more often evaluate the implementation of MISH (human, organizational factors and technology factors) in order to develop further plans for the use of MISH.